SETTLEMENT OF LAND OWNERSHIP DISPUTES BETWEEN MM LACHINSKY AND NY CAECILIA - Marshella, Evi; Arikha Saputra (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
The most fundamental thing about the modus operandi of violations in the implementation of Agrarian Law is the error in understanding, recognizing and applying the conversion of land rights from before and after the enactment of UUPA No. 5 of 1960. Apart from that, the worst thing is that there have been actions, among others, legalizing the mutation of documents with legal defects, the wrong application of the relevant law, changing the measuring papers to pictures of the situation and the mistakes of law enforcers and law enforcement. The results of this study indicate that the Basic Agrarian Law has never regulated that since the enactment of the Law, lands owned by citizens and foreigners have become land controlled by the State. Conversely, when the law is enacted, the old land rights must first apply the conversion provisions that are relevant to the position of the case, in this case are Article 1 paragraph (3), (4), (5) Provisions Conversion of UUPA and Article 12. These regulations are actually looser for foreign citizens who are being burdened with former rightsground lease. This concession and protection are explicitly or implicitly stated in these regulations, namely when there are obstacles for foreign nationals to obtain land conversion e.I dobecome property rights based on Article 1 paragraph (1) of the UUPA Conversion Provisions No. 5 of 1960, then article 1 paragraph (3) protects foreign ownership through conversion to building use rights referred to in article 35 paragraph (1) UUPA No. 5 of 1960. Whereas according to Article 36 paragraph (1) point a. Building use rights are forcitizen Indonesian only.